CORELATION OF GLOBAL LONGITUDINAL STRAIN (GLS) – LEFT VENTRICLE AND SOLUBLE SUPRESSION OF TUMORGENICITY 2 (sST2) IN ACUTE HEART FAILURE WITH SYSTOLIC DYSFUNCTION - Herlina Yulidia; Muhammad Aminuddin; Budi S Pikir (Jurnal Kardiologi Indonesia, 2018)
Background : Assessment of left ventricular function in patients with acute heart failure is important for prognostication, determination of treatment plan, for decisions related to expensive device therapies and for assessing response to treatment. Echocardiography is the "gold standard" of assessing left ventricular function, and in establishing a diagnosis of heart failure. Left ventricular Global Longitudinal Strain (GLS) assessed through Speckle Tracking Echocardiography (STE) is currently considered sensitive in assessing left ventricular motion, by analyzing multidimensional myocardial deformation . s ST2 used to be correlated with stretch miocard and inhibid ligand of IL-33 wich also inhibit the cardioprotectve effect. Objective : To prove the positive correlation between GLS-left ventricle with soluble ST2. Methods : This is a correlational study with cosecutive sampling technique. Thirty subjects participate in this reseach and each subject underwent echocardiography and GLS-left ventricle and soluble ST2 blood examination. The correlation between GLS-left ventricle and soluble ST2 were evaluated using Spearman correlation test. Results : There is a strong, significant, positive correlation between the GLS-left ventricle with soluble ST2 (r = 0.99 and p = 0.0001). Conclusion : There is a strong, significant, positive correlation between the GLS- left ventricle with soluble ST2. Keywords : acute heart failure, systolic dysfunction, global longitudinal strain, soluble ST2.